Prophylactic intracameral vancomycin: efficacy in preventing endophthalmitis after cataract surgery (IMC Journal of Medical Science, 2017)
Background and objective: Post Operative endophthalmitis is rare but devastating complication in ocular surgery. The present study determined the efficacy of intracameral vancomycin after phaco-emusification cataract surgery to prevent endophthalmitis.Method: A total of 768 cases who had undergone phaco-emusification cataract surgery were included in the study. Every alternate patient received 0.5 ml injection of vancomycin (1mg in 0.1 ml) in the anterior chamber after completion of phaco-emulcification and formation of anterior chamber. All the patients were examined for symptoms and signs of bacterial endophthalmitis at 24 hrs, 7 days, 15 days and subsequently at 1, 3 and 6 months following surgery.Results: No endophthalmitis case was recorded at any time period during 6 month follow up in either group. However, significantly higher number of cases in vancomycin group had cells in anterior chamber and disturbances in visual acuity at day 15 following surgery.Conclusion: Vancomycin did not have any prophylactic role in preventing endophthalmitis. Proper aseptic measures are important to prevent any infection in ocular surgery.IMC J Med Sci 2016; 10(1): 24-28